Answer: The coefficient we should change first is for
.
Step-by-step explanation:
The given reaction equation is as follows.
![Al + Ni(NO_(3))_(2) \rightarrow Al(NO_(3))_(3) + Ni](https://img.qammunity.org/2022/formulas/chemistry/college/5hwslo27aaetw2s0wsankivjfuytodhq84.png)
Here, number of atoms present on reactant side are as follows.
- Al = 1
- Ni = 1
= 2
Number of atoms present on the product side are as follows.
- Al = 1
- Ni = 1
= 3
To balance this equation, multiply Al by 2 and
by 3 on reactant side. Also, multiply
by 2 and Ni by 3 on the product side.
Hence, the equation can be rewritten as follows.
![2Al + 3Ni(NO_(3))_(2) \rightarrow 2Al(NO_(3))_(3) + 3Ni](https://img.qammunity.org/2022/formulas/chemistry/college/c3fnhupna8a9b99ydb0decyixat8mgftfe.png)
Now, number of atoms present on reactant side are as follows.
- Al = 2
- Ni = 3
= 6
Number of atoms present on product side are as follows.
- Al = 2
- Ni = 3
= 6
Since, the atoms on both reactant and product side are same. Hence, it is now a balanced chemical equation.
Thus, we can conclude that the coefficient we should change first is for
.